2015
DOI: 10.1161/hypertensionaha.114.04670
|View full text |Cite
|
Sign up to set email alerts
|

IgG Receptor FcγRIIB Plays a Key Role in Obesity-Induced Hypertension

Abstract: There is a well-recognized association between obesity, inflammation, and hypertension. Why obesity causes hypertension is poorly understood. We previously demonstrated using a C-reactive protein (CRP) transgenic mouse that CRP induces hypertension that is related to NO deficiency. Our prior work in cultured endothelial cells identified the Fcγ receptor IIB (FcγRIIB) as the receptor for CRP whereby it antagonizes endothelial NO synthase. Recognizing known associations between CRP and obesity and hypertension i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…(17). Consistent with previous reports (23,24), we found that neither plasma CRP nor SAP was elevated by diet-induced obesity in mice (Supplemental Figure 7, A and B). However, since SAP is the acute-phase reactant pentraxin in mice and CRP is not (25,26), and, as such, SAP abundance may change earlier during the genesis of obesity, we compared the development of obesity-induced insulin resistance in SAP +/+ with that of SAP -/-mice.…”
Section: Hfd-fed Fcγriibsupporting
confidence: 92%
See 1 more Smart Citation
“…(17). Consistent with previous reports (23,24), we found that neither plasma CRP nor SAP was elevated by diet-induced obesity in mice (Supplemental Figure 7, A and B). However, since SAP is the acute-phase reactant pentraxin in mice and CRP is not (25,26), and, as such, SAP abundance may change earlier during the genesis of obesity, we compared the development of obesity-induced insulin resistance in SAP +/+ with that of SAP -/-mice.…”
Section: Hfd-fed Fcγriibsupporting
confidence: 92%
“…However, it was entirely unknown whether FcγRIIB, CRP, the murine CRP-equivalent acute-phase reactant SAP, the classical receptor ligand IgG, or any related mechanisms participate in obesity-induced insulin resistance. A role for FcγRIIB in obesity-related disease was first demonstrated when we determined that mice globally deficient in the receptor are protected from obesity-induced hypertension (24). Although further elucidation of the processes whereby the receptor causes blood pressure elevation in obesity is required, the available evidence to date suggests that the hypertension and insulin resistance that complicate obesity may have shared mechanistic origins centered on FcγRIIB.…”
Section: Figure 5 Igg From Hfd-fed Mice Attenuates Insulin-induced Ementioning
confidence: 99%
“…Approaches targeting FcgammaRIIB may potentially offer new means to treat hypertension in obese individuals. 79 Although antibodies seem to be important, B cells may exert their effects through B-cell specific contribution to cytokine production, such as tumor necrosis factor-α, 80 which has been shown to be prohypertensive and proatherosclerotic. Role of macrophages in hypertension and atherosclerosis is evident 67,81 and closely linked to NADPH oxidases, which are abundant within both monocytes and macrophages.…”
Section: Inflammatory Mechanisms Of Hypertension Are Linked To Oxidatmentioning
confidence: 99%
“…FcγRI and FcγRII expression on cultured human aortic endothelial cells was shown to mediate IgG internalisation, cytokine production, upregulation of adhesion molecules and activation by CRP in vitro [63]. Furthermore, FcγRIIB has been implicated in the pathogenesis of obesity-induced hypertension, via IgG-mediated attenuation of endothelial NO synthase activity [64]. The extent of FcγR expression on renal endothelial cells is less clear [65].…”
Section: Fcγr Function In Immune Cellsmentioning
confidence: 99%